The Role of Organizational Culture and Transformational Leadership in Improving Citizenship Behavior through Self-Efficacy and Trust - Afiatin Nisa; Sri Setyaningsih; Suhendra (International Journal of Technology and Education Research, 2025)
This study aims to find strategies and ways to improve Organizational Citizenship Behavior. This research method uses quantitative methods with path analysis techniques and SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management) analysis. The population in this study was 531 teachers and the sample was 266 permanent teachers of Private High Schools in Depok City. Based on the results of the SITOREM analysis, the optimization results in efforts to improve OCB are as follows: Priority Order for Handling Indicators: 1st Altruism, 2nd Civic Virtue, 3rd Providing motivating inspiration, 4th Psychological Condition, 5th Prestige for Success, 6th Readiness to accept risks, 7th Confidence in ability and strength then Indicators Maintained or Developed: 1st Conscientiousness, 2nd Sportsmanship, 3rd Courtesy, 4th Boosterism, 5th Artifacts, 6th Shared Values, 7th Agreed upon norms, 8th Basic Assumptions, 9th As a role model, 10th Stimulating subordinates to be creative and innovative, 11th Providing instructional support, 12th Providing individual attention, 13th Task Frequency, 14th Task Complexity, 15th Task Completion Time, 16th Previous Experience, 17th Social Persuasion, 18th Model of Successful Behavior, 19th Optimism, 20th Honesty and Responsibility, 21st Good working relationships, 22nd Being cooperative and working with a team